Examining the Effect of Leader Behavior and Employee Commitment on Employee Performance - Dewi, Ni Made Rai Candra; Ardani, Wayan; Widani, Ni Made (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
The purpose of this study was to determine the effect of leader behavior and employee commitment on employee performance. The population of this research was the employees of PT. Sanur Jaya Utama, totaling 43 employees and all of them were being the respondents of this research. The collection of research data was carried out by means of questionnaires, interviews and observations. This study used multiple regression analysis techniques. This study revealed that leader behavior had a positive and significant effect on employee performance, work commitment had a positive and significant effect on employee performance, leader behavior and employee commitment simultaneously had a positive and significant effect on employee performance at PT. Sanur Jaya Utama. This study is expected to be a reference for the management of PT. Sanur Jaya Utama and other enterprises that leader behavior and employee commitment are very important factors in improving employee performance.